2017
DOI: 10.1080/17453674.2017.1409941
|View full text |Cite
|
Sign up to set email alerts
|

Good inter- and intraobserver reliability for assessment of the slip angle in 77 hip radiographs of children with a slipped capital femoral epiphysis

Abstract: Background and purposeThe decision on and the outcome of treatment for a slipped capital femoral epiphysis (SCFE) depend on the severity of the slip. In 2015, web-based registration was introduced into the Swedish Pediatric Orthopedic Quality (SPOQ) register. To determine whether the inclusion of commonly used methods in Sweden for radiographic measurement of SCFE (the calcar femorale [CF] method and the Billing method) is justified, we measured the inter- and intraobserver reliability of these 2 measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Furthermore, the radiographic assessments and measurements were performed by a resident orthopedic surgeon and not a radiologist. Studies have shown good inter-observer reliability for radiographic measurements between observers with varying experience (Tiderius et al 2004, Herngren et al 2018 and that radiologic technologists with appropriate training can interpret radiographs accurately (Piper et al 2005, Woznitza et al 2018. In our study, the observer had extensive training prior to the data collection and continuous support from senior orthopedic consultants during the readings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the radiographic assessments and measurements were performed by a resident orthopedic surgeon and not a radiologist. Studies have shown good inter-observer reliability for radiographic measurements between observers with varying experience (Tiderius et al 2004, Herngren et al 2018 and that radiologic technologists with appropriate training can interpret radiographs accurately (Piper et al 2005, Woznitza et al 2018. In our study, the observer had extensive training prior to the data collection and continuous support from senior orthopedic consultants during the readings.…”
Section: Discussionmentioning
confidence: 99%
“…For slip angle, intraclass correlation coefficients (ICC) for inter-rater reliability has been reported to be 0.98 with intrarater reliability having a mean difference below 1 degree. 17 A second study found slip angle to have an interrater reliability ICC of 0.97 and intrarater reliability of 0.989. 12 Cohen's quadratic weighted kappa statistic has been used to describe reliability for measurements of the screw within the epiphysis.…”
Section: Methodsmentioning
confidence: 94%
“…Intrarater and inter-rater reliabilities were not calculated, as we do not describe a novel radiographic measurement and reliabilities have been previously reported for the measurements used. For slip angle, intraclass correlation coefficients (ICC) for inter-rater reliability has been reported to be 0.98 with intrarater reliability having a mean difference below 1 degree 17. A second study found slip angle to have an inter-rater reliability ICC of 0.97 and intrarater reliability of 0.989 12.…”
Section: Methodsmentioning
confidence: 98%
“…High intraobserver and interobserver reliability of the epiphyseal shaft angle on radiographic analysis of the slipped capital femoral epiphysis in humans have previously been reported. 10 Additionally, we calculated intraclass and interclass correlation coefficients, finding good reliability between readers. All measurements were performed twice by one examiner and once by another examiner.…”
Section: Methodsmentioning
confidence: 98%